Lutra lutra lutra - Wilson, Don E.; Mittermeier, Russell A. (Zenodo, 2009)
34. Eurasian Otter Lutra lutra French: Loutre d'Europe / German: Eurasischer Fischotter / Spanish: Nutria paleartica Other common names: European Otter Taxonomy. Mustela lutra Linnaeus, 1758, Sweden. The Japanese Otter (L. nippon) is considered by some authors to be a valid species, based on recent morphological and molecular analyses. However, further research is needed to determine its taxonomic status; it is here considered a subspecies of L. lutra. Up to twenty-eight subspecies have been proposed, but a taxonomic revision is needed. Distribution. Wide distribution in the Palearctic: from Europe to Russian Far East, North and South Korea, and Japan; also N Africa, Middle East, C Asia, Sub-Himalayan zone, S India, Sri Lanka, C, E & S China, Taiwan, Indochina, and Sumatra. Descriptive notes. Head-body 50-82 cm, tail 33-50 cm; weight 5-14 kg, adult males are typically 50% larger than females. The Eurasian Otter has a long body and a conical tail. The short, dense pelage is brown to almost black throughout, with slightly paler undersides. The legs are short; the feet are fully webbed and have well-developed claws. There are two to three pairs of mammae. The cranium is large and flat. Dental formula: 13/3, C1/1,P 4/3, M 1/2 = 36. Habitat. Eurasian Otters are found along lakes, ponds, rivers, and streams, and in marshes, swamps, and coastal and estuarine wetlands, from sea level up to 4120 m. They avoid areas of deep water. Food and Feeding. The diet is mainly fish, frogs, and aquatic invertebrates (including crustaceans and crabs). Birds and small mammals (such as rodents and lagomorphs) may be consumed on occasion. In general, the mean proportion offish declines from 94% on seashores, to 71% on lakes and fish ponds, to 64% on rivers and streams. On inland waters, the abundance of crayfish is an essential food item. In Northern Ireland, over 50% of spraints were composed of sticklebacks (Gasterosteus aculeatus), salmonids and cyprinids, with Sticklebacks constituting the most frequently occurring prey category. The frequency of occurrence of eels (Anguilla anguilla) was found to be consistently higher in spraints collected from smaller streams. In eastern Poland,fish constitutes 51% of the food biomass consumed in spring-summer and 40% in autumnwinter, with perch (Perca fluviatilis), pike (Esox lucius), and roach (Rutilus rutilus) being captured most frequently. Amphibians (mainly Rana temporaria) make up 34% of the food biomass in spring-summer and 58% in autumn-winter. The cold season diet depends on river size. On small rivers with forested valleys, Eurasian Otters feed nearly exclusively on amphibians (72-90% of food biomass). As the size of the river increases, and riverside habitat becomes more open (sedge and reed marshes instead of forests), Eurasian Otters shift to catching predominantly fish (up to 76%). In southern Poland, the main component of the diet is fish (47-9%, including brown trout Salmo trutta and rainbow trout Oncorhynchus mykiss). Other important food items are 21-4% frogs (R. temporaria) and 30% birds, small mammals, aquatic and terrestrial invertebrates, and plant debris. In southern Italy, spraint analysis revealed that fish represented the dominant food (57-3% mean volume), followed by amphibians (18:9%) and crayfish (15-6%). Seasonal variations in fish consumption were related to changes in fish activity and to environmental conditions; the importance of fish decreased in winter, when flooding increased water speeds and turbidity, and thus reduced the hunting efficiency of the otters. Hibernating amphibians represented a primary alternative resource. Insects and reptiles were eaten more frequently in summer, while birds predominated during their breeding season. In Hungary, the primary food is fish (89-8% for riverine and 87-5% for backwater habitats); Eurasian Otters living in riverine habitats, compared to backwaters, consume more birds (3-9% and 0-7%, respectively), less mammals (0-5% and 0-9%, respectively), less reptiles and amphibians (5-6% and 10-2%, respectively) and less invertebrates (0-1% and 0-6%, respectively); most fish eaten are small-sized (below 100 g), and the most frequently taken species is Carassius sp. In Iran, the major food items are 38-1% chub (Alburnoides bipunctatus) and 34-8% carp (Cyprinus carpio). Prey are captured with the mouth, but the forepaws are used to handle the prey for consumption. Activity patterns. Mainly nocturnal and crepuscular, but can also be active during the day. Den/restsites are in burrows, among root systems, log jams, or in rock crevices, in close proximity to water. Movements, Home range and Social organization. Eurasian Otters are excellent swimmers and divers. They are usually found no more than a few hundred meters from water, but they may travel several kilometers overland between wetlands. They swim using movements of the hindlegs and tail; usually dives last one or two minutes,five at the most. When traveling on the ground, snow, or ice they may use a combination of running and sliding. Males typically are solitary, whereas females may occur in groups, either with their own young or with unrelated, reproductive females and their young. The straight-line length of a home range may reach an average of 15 km for males and 7 km for females. Males and femalestypically defend their range against members of the same sex, but the home ranges of males may overlap those of several females. Population densities may be one otter per 2-3 km of lakeshore or 5 km ofriver. Breeding. Females are polyestrous, with the cycle lasting four to six weeks; estrus lasts about two weeks. Mating typically occurs in late winter or early spring. The gestation period is 60-63 days and births peak in April or May. The main entrance of bank burrows may open underwater and then slope upward into the bank to a nest chamber that is above the high-water level. Litter size is one to five, usually two to three. The young are born blind and weigh about 130 g at birth. They open their eyes after one month and emerge from the den and begin to swim at two months. They nurse for three to four months and separate from the mother at about one year. Sexual maturity is attained after two or three years. Status and Conservation. CITES Appendix I. Classified as Near Threatened in The IUCN Red List. The Japanese Otter, once common, has no recent confirmed sightings and may be extinct. Eurasian Otters are vulnerable to water pollution because their bodies accumulate contaminants and heavy metals, which affect reproduction. They also are killed accidentally on roads and deliberately for their fur. Bibliography. Chruszcz et al. (2007), Conroy et al. (1998), Francis (2008), Imaizumi & Yoshiyuki (1989), Kruuk & Conroy (1991), Kruuk et al. (1989), Lanszki & Sallai (2006), Lanszki & Szeles (2006), Philcox et al. (1999), Preston et al. (2006), Prigioni et al. (2006), Rasooli et al. (2007), Stroganov (1969), Suzuki et al. (1996), Wozencraft (2005, 2008). : Published as part of Don E. Wilson & Russell A. Mittermeier, 2009, Mustelidae, pp. 564-656 in Handbook of the Mammals of the World – Volume 1 Carnivores, Barcelona :Lynx Edicions on pages 644-645, DOI: 10.5281/zenodo.5714044